NEED ANALYSIS OF ENGLISH FOR TOURISM AND EVENT LEARNING DESIGN DURING HYBRID-TECHNOLOGY ERA - Nova, Muhamad; Lastari, Ni Kadek Herna (Premise: Journal of English Education and Applied Linguistics, 2024)
With the development of the economy and tourism in Indonesia after the pandemic, there are some changes in the industry needs, especially in MICE and Event. The change in the shifting use of hybrid technology requires adjustments in skills and knowledge applied in MICE and Event industry, especially the need for communication skills in English. The current study focuses on the need for English for Tourism and Event learning design to support the hybrid-technology era. This study employed a qualitative approach with a narrative inquiry design. The current study took eight students as participants who had taken the English for Tourism and Event class and had already finished their MICE and Event industry internship. The data was gained through field observation, questionnaire distribution, and semi-structured interviews. The data obtained was analyzed through three phases: condensation, display, and conclusion drawing. Based on the result, 16 learning topics related to communication skills are needed and used by the internship students in the industry. Learning material development is required to fulfill the industry's needs. It implies that the current English learning design needs to be updated with the rapid changes in the MICE industry.